5PSQ-076 Switching biologic treatments: experience of a regional hospital. (March 2019) - Retamero, A; Grados, D; Cucurell, M; Sanchez, X; Pares, RM; Serrais, J; Ferrandez, D
Abstract : Background: Due to the approval of new biological treatments (BT) with innovative mechanisms of action (MOA), patients have more options to achieve clinical remission. Purpose: To analyse the reasons for switching to BT, evaluate their effectiveness and the costs associated. Material and methods: Retrospective study conducted between January to December 2017 in a regional hospital with a reference area of 1 10 000 inhabitants and 220 BT. All patients who switched their BT were included. Data on relevant patient characteristics, diagnostics and treatment were collected. Total drug costs were calculated from Botplus (September 2018). In the case of weight-dependent doses a standard weight of 70 kg had been considered. Statistical analysis was carried out with SPSS Statistics v.22. Results: Thirty-eight (19.0%) patients were included; 12 (31.6%) males; and 48.9 (12.5) years' old. Distribution by diagnostics: 17 (44.7%) rheumatoid arthritis (RA), eight (21.1%) spondyloarthropathies, five (13.1%) psoriatic arthritis, three (7.9%) psoriasis, three (7.9) Crohn's disease and two (5.3%) ulcerative colitis. In 32 (84.2%) patients, the specialist waited for a minimum of 12 weeks to switch to BT (except in cases of adverse effects). Nineteen (50.0%) patients had received more than one BT previously. Two BT (infliximab) vs one BT (etanercept) were biosimilars. Previous vs new BT: 31 (81.6%) vs 14 (36.8%) anti-TNFα and seven (18.4%) vs 24 (63.2%) drugs with different MOA (Chi square 15.75; p<0.001). Only four (10.5%) patients remained with an anti-TNFα after the switch. Reasons for switching: 29 (76.3%) loss or lack of response, eight (21.1%) adverse effects and one (2.6%) new comorbidity that contraindicated the BT. At the moment of the analysis, 22 (57.9%) BT remained active while 16 (42.1%) were stopped or switched again. Among the 22 patients in the same BT, 10 (45.6%) were in remission, six (27.2%) had low activity and six (27.2%) had moderate activity of the disease. The incremental cost of switching was €46, 908.75 annually. Conclusion: Switching of BT in our hospital is common. The most frequent reasons were the loss or lack of response and the presence of adverse effects. In most of the cases, there was a change in the pharmacological target, although in recent published studies the proportion of TNF cyclers and MOA switchers is similar. 1 Despite the switching of BT, the rate of response was high. Switching BT meant an increase to our budget. References and/or acknowledgements: 1. Adv Ther2017;34:1936–52. No conflict of interest.